2007
DOI: 10.1002/jmv.20850
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude toward HIV voluntary counseling and testing services among pregnant women attending an antenatal clinic in Sudan

Abstract: Human immunodeficiency virus (HIV) infection and the development of the acquired immunodeficiency syndrome (AIDS) are increasing at an alarming rate especially in the sub-Saharan region. Pregnant women susceptible to HIV and its transmission to the fetus provide a unique opportunity for implementing preventive strategy against HIV infection of newborn babies. During the period of August-December 2005 a cross-sectional study was conducted at the Fath-Elrahman Elbashir antenatal clinic, Khartoum Teaching Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
46
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 18 publications
12
46
2
1
Order By: Relevance
“…Employed pregnant women accepted VCT at higher rates than unemployed married women. Similar results were obtained in a Vietnamese study [54] and in a Sudanese study [41] . The researchers suggested that when women leave the home and are employed, they have greater access to information about VCT compared to unemployed married women who spent most of their time at home [37] .…”
Section: Marital Status: Fabiani Et Alsupporting
confidence: 89%
See 4 more Smart Citations
“…Employed pregnant women accepted VCT at higher rates than unemployed married women. Similar results were obtained in a Vietnamese study [54] and in a Sudanese study [41] . The researchers suggested that when women leave the home and are employed, they have greater access to information about VCT compared to unemployed married women who spent most of their time at home [37] .…”
Section: Marital Status: Fabiani Et Alsupporting
confidence: 89%
“…Dube and Nkosi [43] found that half of the women in their study felt 50% of respondents expressed willingness to be tested in a Chinese study by Li et al [36] and in an Ethiopian study by Moges and Amberbir [37] ; in contrast, other studies reported higher willingness to be tested (more than 75% of respondents expressed willingness to be tested) [38][39][40] . Some African studies demonstrated significant gaps between the willingness of pregnant women to receive HIV testing and their actual testing rates, as in studies from Sudan [41] and Tanzania [42] . Similarly, a South African study showed that pregnant women had a good level of knowledge and understanding about HIV testing in pregnancy, and their perceptions of HIV testing were positive, but they were not consistent with their behavior.…”
Section: Fear Of the Test Resultsmentioning
confidence: 99%
See 3 more Smart Citations